2017
DOI: 10.1158/1078-0432.ccr-16-2142
|View full text |Cite|
|
Sign up to set email alerts
|

PI3K Inhibition Reduces Mammary Tumor Growth and Facilitates Antitumor Immunity and Anti-PD1 Responses

Abstract: Purpose Metastatic breast cancers continue to elude current therapeutic strategies, including those utilizing PI3K inhibitors. Given the prominent role of PI3Kα,β in tumor growth and PI3Kγ,δ in immune cell function, we sought to determine whether PI3K inhibition altered anti-tumor immunity. Experimental Design The effect of PI3K inhibition on tumor growth, metastasis, and anti-tumor immune response was characterized in mouse models utilizing orthotopic implants of 4T1 or PyMT mammary tumors into syngeneic or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 50 publications
3
93
0
Order By: Relevance
“…During T-cell activation, Src homology 2 domain-containing leukocyte protein of 76 kDa (SLP76) associates with PI3K subunit p85, leading to the downstream Akt activation (8). Inhibition of PI3K isoform promoted robust CD8 þ T-cell activation, improved antitumor immunity, and host survival by enhancing the cytokines production of cytotoxic lymphocytes (9,10). PI3K/Akt/mTOR complex has also been shown to be involved in the differentiation of various immunosuppressive T-cell subsets including Foxp3 þ Treg cell and tumor-associated macrophages (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…During T-cell activation, Src homology 2 domain-containing leukocyte protein of 76 kDa (SLP76) associates with PI3K subunit p85, leading to the downstream Akt activation (8). Inhibition of PI3K isoform promoted robust CD8 þ T-cell activation, improved antitumor immunity, and host survival by enhancing the cytokines production of cytotoxic lymphocytes (9,10). PI3K/Akt/mTOR complex has also been shown to be involved in the differentiation of various immunosuppressive T-cell subsets including Foxp3 þ Treg cell and tumor-associated macrophages (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we speculated that hyper-activated PI3K-AKT pathway in tumor cells might play a major role in suppressing immune infiltration in cluster 2, such as through TGF-b secretion and CAF differentiation. In particular, previous studies have revealed that pan-PI3K inhibition enhances antitumor immunity and anti-PD1 response in breast cancer (45).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these TAM reprogramming strategies are currently under active clinical evaluation 39 . Notably, CD40 agonists work through activating CD40L-downstream NF-kB pathway 87,89 ; HDAC inhibitors work through altering histone modi cations 86,90,91 ; PI3Kγ inhibitors work through stimulating NF-κB activation while inhibiting C/EBPβ activation 88,92,93 ; and creatine uptake works through regulating cytokine responses 40 . Our discovery of MAO-A as a critical regulator of TAM polarization through modulating oxidative stress provides a new drug target and a new mechanism of action (MOA) for expanding TAM-repolarizing strategies.…”
Section: Discussionmentioning
confidence: 99%